Nanozyme-mediated signal amplification for ultrasensitive photoelectrochemical sensing of Staphylococcus aureus based on Cu–C3N4–TiO2 heterostructure - Luo, Siyu; Liu, Fanglei; Gu, Siyu; Chen, Ke; Yang, Guohai; Gu, Yingqiu; Cao, Juntao; Qu, Lu-Lu (Biosensors & bioelectronics, 2022)
Food-borne pathogens are one of the leading causes of food poisoning, which vigorously affect food safety and human health. Therefore, the development of early and rapid detection methods for food pollution evaluation is the key to food safety and quality control. Herein, a simple and inexpensive photoelectrochemical (PEC) sensor is developed for highly selective and ultrasensitive detection of Staphylococcus aureus (S. aureus). The technique is based on “signal-off” that employs Cu–C3N4–TiO2 heterostructures as photoactive materials and monolayer Cu–C3N4 nanozyme as a signal amplifier. In the presence of S. aureus, the aptamer-modified Cu–C3N4 (Cu–C3N4@Apt, a signal amplifier) and S. aureus were specifically anchored on the surface of the ligand-modified photoelectrode. The Cu–C3N4@Apt nanozyme acted as a peroxidase to catalyze the oxidation of 4-chloro-1-naphthol (4-CN) to produce insoluble precipitate on the electrode surface and resulted in a significant decrease in photocurrent. Based on the signal-amplification by the Cu–C3N4@Apt nanozyme, the constructed PEC sensor demonstrated a wide linear range between 10–108 CFU/mL for the S. aureus detection with the detection limit (LOD) as low as 3.40 CFU/mL. Furthermore, the PEC sensor was capable of determining S. aureus in spiked orange juice and milk, with the recovery of 91%–113%, indicating the reliability of the sensor for S. aureus detection in real samples. This investigation provides a feasible strategy for the design of highly selective and ultrasensitive PEC sensors to determine analytes in complex systems.